Genetic diversity in Cichla monoculus (Spix and Agassiz, 1931) populations: Implications for management and conservation - Santos, Carlos Henrique dos Anjos dos; Sousa, Carolina Fernandes Silva de; Nazaré Paula-Silva, Maria de; Val, Adalberto Luis; Val, Vera Maria Fonseca Almeida e (American Journal of Environmental Sciences, 2012)
Problem statement: The object of this study was to examine the genetic structure and gene flow in Cichla monoculus populations in seven varzea lakes of the Solimoes River using Randomly Amplified Polymorphic DNA (RAPD) markers, to monitor the region where petroleum is transported in the Amazon basin. Approach: The loss of genetic diversity is one of the main factors leading to reduced evolutionary potential in species of fish. In this context, this paper seeks to understand how the influence of the stretch of pipeline in the Solimoes River between the cities of Manaus-Coari influences the genetic structure of C. monoculus. For this we measured the level of genetic diversity and structure of the species in the studied stretch. Results: Proportions of polymorphic loci varied from 8.7-39.7% in analyzed populations. Low heterozygosis levels were detected (He = 0.1652) and highly structured populations in the seven lakes with low gene flow (Nm = 0.7025) among all fish studied. Unexpected differentiation was found between fishes among the lakes. Fish populations from lakes closest to Manaus (human population of ~2 million) are different from those occurring in lakes closest to the Coari region (close proximity to petroleum barge transfer terminals). Conclusion/Recommendations: Differentiation can be explained by natural causes. This study identifies antropogenic activities influencing this species overall. Since industrial fishing is prevalent due to the high economic value of C. monoculus. Also, this species posses behavioral characteristics that are desirable in sports fishing. Management and conservation of this species will be necessary in the near future to recover genetic variability levels in each lake and allow gene flow among them. Further studies are needed to better understand the differentiation among populations. © 2012 Science Publications.
Keywords: Anthropogenic Effect; Cichlid; Conservation Genetics; Conservation Management; Evolutionary Biology; Gene Flow; Genetic Marker; Genetic Structure; Genetic Variation; Human Activity; Muscle; Petroleum; Pipeline; Skeleton; Species Conservations; Sport Fishing; Amazon Basin; Amazonas; Solimoes River; Bairdiella Rhonchus; Cichla Monoculus; Pisces